Paulinella, a model for understanding plastid primary endosymbiosis. Issue 4 (5th May 2020) - Gabr, Arwa; Grossman, Arthur R.; Bhattacharya, Debashish
Abstract : The uptake and conversion of a free‐living cyanobacterium into a photosynthetic organelle by the single‐celled Archaeplastida ancestor helped transform the biosphere from low to high oxygen. There are two documented, independent cases of plastid primary endosymbiosis. The first is the well‐studied instance in Archaeplastida that occurred ca. 1.6 billion years ago, whereas the second occurred 90–140 million years ago, establishing a permanent photosynthetic compartment (the chromatophore) in amoebae in the genus Paulinella . Here, we briefly summarize knowledge about plastid origin in the Archaeplastida and then focus on Paulinella . In particular, we describe features of the Paulinella chromatophore that make it a model for examining earlier events in the evolution of photosynthetic organelles. Our review stresses recently gained insights into the evolution of chromatophore and nuclear encoded DNA sequences in Paulinella, metabolic connectivity between the endosymbiont and cytoplasm, and systems that target proteins into the chromatophore. We also describe future work with Paulinella, and the potential rewards and challenges associated with developing further this model system.